Análisis del desarrollo sostenible de la industria polimérica en Colombia. (2022)
The polymer industry has been expanding throughout the world over the last decades, being a field that allows the development and innovation of tools, products and mechanisms, directly molding such versatile and multifaceted elements that favor the daily life of the being. human, to the point that it can be seen how society is currently plagued by plastic elements at levels never seen before. The contamination that has been derived from this global overproduction lies not only in the long life of a plastic but also in the agents and capacity for contamination that they release during their degradation process. This is where the methodology widely used today for different sectors of society comes in, such as the vision and implementation of sustainable development.